Valve-Pump Parallel Variable Mode Control for Complex Speed Regulation Processes. (3rd September 2018) - Ding, Haigang; Song, Henan; Zhao, Jiyun; Lin, Chaowen
Abstract : To improve comprehensive performances of hydraulic systems with complex speed regulation processes, this paper proposes a new control scheme, valve-pump parallel variable mode control, which can change control modes according to control requirements and adjust the proportion of valve control and pump control in the speed regulation process. In this paper, we design a valve-pump parallel variable mode control system, explain its working principle, establish its mathematical model, analyse the influences of valve control on the system parameters, and at last, build an experimental system to carry out an experimental research. The experimental results show that during the speed regulation process, control modes could vary with control requirements, the switch between different control modes is smooth and meets expectations, and the proposed control approach can achieve excellent comprehensive performances for complex speed regulation, such as low-speed stability, fast response to load disturbance, and high efficiency. The valve-pump parallel variable mode control makes hydraulic control systems more flexible and suitable and enrich the current control schemes of hydraulic speed regulation systems.